The Use of Social Stories to Improve Social Interaction Skills of Students With Adhd in Inclusive Classrooms at Giwangan Elementary School Yogyakarta - Imelda Seprina Hanin; Pujaningsih (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aimed to improve the social interaction skills of a student with Attention Deficit Hyperactivity Disorder (ADHD) in an inclusive classroom through the implementation of the Social Stories method. The study was conducted at Giwangan Elementary School, Yogyakarta, involving one fifth-grade student with ADHD. This research employed Classroom Action Research based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection, and was carried out in two cycles. Data were collected through observation, interviews, documentation, and field notes, and analyzed using descriptive qualitative techniques supported by simple quantitative measures. The findings indicated a progressive improvement in the student’s social interaction skills. In Cycle I, the average achievement of social interaction indicators reached 54%, which did not meet the minimum success criterion (≥75%). Following improvements in instructional strategies, including structured storytelling, repeated exposure, intensive support, and consistent positive reinforcement, the score increased to 93% in Cycle II. The student showed improved ability in turn-taking, rule-following, cooperation, and peer interaction. These findings suggest that Social Stories can be an effective intervention to support social interaction development for students with ADHD in inclusive classroom contexts, particularly in case-based applications.